Improving young learners’ retention of English vocabulary through multiple intelligences approach - Hoàng, Thị Thu Hồng (2020)
Traditional teaching methods in general and,in particular, teaching vocabulary tend to treat students as a homogeneous group. Teachers have tendencies to present the same in-class exercises and activities to all learners and expect the same outcome. Sometimes, students do not show their interest in studying such new things in such mentioned stable old ways. Using Howard Gardner (1983)’s Multiple Intelligence Theorycan be a good model for vocabulary teaching when it has various implications for educators in terms of classroom instructions. This action research is conducted with the aim of discovering whether students can improve their retention ofEnglish vocabulary through Multiple Intelligences Approach. Specifically, the study will try to answer the following questionwhose resultwill be used for later discussion: To what extent do activities based on Multiple Intelligence Approach contribute to young learners’ retention of English Vocabulary?